Morphological differentiation in the widespread fish Galaxias maculatus: do darker environments imply bigger eyes? - Rojo, Javier Hernán; Rodriguez, Patricia Laura; Boy, Claudia Clementina (Hydrobiologia)
The visual capacity of aquatic organisms is, in general, related to light penetration in the water. Therefore, aquatic environments that differ in color can potentially contribute to species polymorphism, especially in fish. In this study, we explore the relationship between light quality and intensity in water bodies and the eye and mouth size in Galaxias maculatus, one of the most widespread fish. Fish morphology was studied photographically, and the vertical attenuation coefficient of light (Kd) was measured in five aquatic systems: two humic lakes, two estuaries, and one river. Water color was also estimated as absorbance at 440 nm. In those environments with less light penetration and darker water color, we observed bigger eyes and, additionally, larger mouths. The darkness of water bodies was mainly related to water color associated with humic substances. As G. maculatus is known to be a visual predator, our results suggest that bigger eyes increase visual capacity in darker environments, which would result in improved feeding rates, also supported by larger mouth length. Fil: Rojo, Javier Hernán. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Rodriguez, Patricia Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina Fil: Boy, Claudia Clementina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina